Desain dan Uji Coba E-Book Berbasis POE (Prediction-Observation-Explanation) Pada Materi Laju Reaksi - Neti Afrianis; Intan Permata Bunda (LPPM Universitas Negeri Jakarta, 2020)
This research was instigated by the importance of learning facility technology based for students on Chemistry Subject. It was aimed at knowing the validity and practicality of media that was designed. This research was conducted to the eleventh-grade students of MIPA 6 at State Senior High School 1 Pekanbaru in the Academic Year 2019/2020, and they were 12. It was Research and Development with Borg and Gall modified model. The techniques of collecting the data were observation, interview, questionnaire, and documentation. The final product was in the form of instructional media that was valid. POE (Prediction, Observation and Explanation) based Electronic Book on Reaction Rate lesson had been tested valid by experts of media and material with 90.13% mean percentage (very valid), and practical by 2 Chemistry subject teachers and 12 students with 91.41% mean percentage (very valid). Based on the result, it could be concluded that POE based Electronic Book on Reaction Rate lesson was valid and practical, so the next phase could be tested. Keywords Chemistry instructional model, electronic book, POE (Prediction, Observation and Explanation), reaction rate